Physicians’ and patients’ perceived risks of chronic pain medication and co-medications in Quebec, Canada: a cross-sectional study - Gwenaëlle De Clifford-Faugère; Anaïs Lacasse; Hermine Lore Nguena Nguefack; Marimée Godbout-Parent; Aline Boulanger; Nancy Julien (BMC Primary Care)
Abstract Background The risks associated with medications and co-medications for chronic pain (CP) can influence a physician’s choice of drugs and dosages, as well as a patient’s adherence to the medication. High-quality care requires patients to participate in medication decisions. This study aimed to compare perceived risks of medications and co-medications between physicians and persons living with CP. Methods This cross-sectional survey conducted in Quebec, Canada, included 83 physicians (snowball sampling) and 141 persons living with CP (convenience sampling). Perceived risks of adverse drug reaction of pain medications and co-medications were assessed using 0–10 numerical scales (0 = no risk, 10 = very high risk). An arbitrary cutoff point of 2-points was used to ease the interpretation of our data. Physicians scored the 36 medication subclasses of the Medication Quantification Scale 4.0 (MQS 4.0) through an online survey, while CP patients scored the medication subclasses they had taken in the last three months through telephone interviews. Results Persons living with CP consistently perceived lower risks of adverse drug reaction compared to physicians. For eight subclasses, the difference in the mean perceived risk score was > 2 points and statistically significant (p < 0.05): non-specific oral NSAIDs, acetaminophen in combination with an opioid, short-acting opioids, long-acting opioids, tricyclic antidepressants, antipsychotics, benzodiazepines, and medical cannabis. Conclusions Divergent risk perceptions between physicians and patients underscore the necessity of facilitating a more extensive discussion on medications and co-medications risks to empower patients to make informed decisions and participate in shared decision-making regarding their treatments.